2019
DOI: 10.3390/nu11020385
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Intervention of Dietary Counseling for Overweight and Obese Pregnant Women in the Consumption of Sugars and Energy

Abstract: Objective: Evaluate if an intervention based on nutritional counseling decreases total sugars and energy consumption in overweight and obese pregnant women, compared to their previous consumption and compared to women who only received routine counseling. Methods: Randomized study of two groups: dietary counseling (Intervention Group: IG) and routine counseling (Control Group: CG). The intervention consisted of three educational sessions focused on decreasing intake of foods that most contribute to sugars cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 32 publications
0
37
0
2
Order By: Relevance
“…According to the theory of metabolic programming, environmental factors and lifestyle, including diet, during the pregnancy of the mother, among other effects, has an influence on the health and disease risk in the later life of the offspring [6]. Obesity or malnutrition in a future mother is considered to be one of the most important factors determining intrauterine fetal development [7,8]. Elimination diets, which have recently been fashionable among young mothers, may cause nutritional deficiencies, which in turn can lead to complications with the pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…According to the theory of metabolic programming, environmental factors and lifestyle, including diet, during the pregnancy of the mother, among other effects, has an influence on the health and disease risk in the later life of the offspring [6]. Obesity or malnutrition in a future mother is considered to be one of the most important factors determining intrauterine fetal development [7,8]. Elimination diets, which have recently been fashionable among young mothers, may cause nutritional deficiencies, which in turn can lead to complications with the pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…29,31 We also revealed in a previous paper that women randomized to the dietary counseling intervention significantly decreased their consumption of sugar and energy. 22 A recent review by Cochrane concluded that lifestyle interventions possibly reduce the risk of GDM, but more high-quality clinical trials are needed. 32…”
Section: Resultsmentioning
confidence: 99%
“…A validated semiquantitative food frequency questionnaire (FFQ) that comprises 80 food items was completed by the participants to evaluate their energy and sugar intake at the first and the 35 to 37 weeks' visits. 22 Taking advantage of the biological samples (blood and urine) already planned as routine in the PHCC, an additional blood extraction of 20 mL to determine glucose (GOD-PAP commercial kit, Química Clínica Aplicada SA, Amposta, Spain), insulin (radioimmunoassay; sensitivity¼0.5 mIU/mL, intra-assay coefficient of variation¼8.6, inter-assay coefficient of variation¼10.2), and the lipid profile (dry analytical methodology, Vitros, Johnson & Johnson, New Brunswick, NJ) was carried out at the first prenatal visit and at 24 to 28 weeks of pregnancy. CHIMINO allows for collecting additional fasting venous samples along with the routine PHCC blood extractions.…”
Section: Measurements and Data Collectionmentioning
confidence: 99%
“…References are included for each study in Table 1 with trial/cohort names or locations when names were unavailable. Six studies were conducted in the U.S. 6,7,9,[11][12][13]16,25 In addition, three studies were conducted in Spain, 1,2,23,26 two each in the U.K., 22,24 Norway, 5,21 and Japan 3,4 ; and one each in Mexico, 18 Italy, 19 Poland, 17 Iceland, 14 Finland, 10 the Netherlands, 8 China, 15 and Malaysia. 20…”
Section: Description Of the Evidencementioning
confidence: 99%
“…2,[6][7][8][9][11][12][13]21,[23][24][25][26] Nine studies did not report race/ethnicity. 1,3,5,10,14,15,[17][18][19] Yong et al 20 reported that 89 percent of the participants were Malay and Tajima et al 4 noted that 100 percent of their participants were Japanese. Zhu et al 16 reported that the participants were predominantly Hispanic (approximately 41.3 percent) and Al Wattar et al 22 noted that the participants were predominantly Asian (approximately 43.7 percent).…”
Section: Subject Characteristicsmentioning
confidence: 99%